2015
DOI: 10.1007/s10803-015-2535-1
|View full text |Cite
|
Sign up to set email alerts
|

Educational Experiences and Needs of Higher Education Students with Autism Spectrum Disorder

Abstract: Little research directly examines the needs of post-secondary students with ASD. The experiences and support needs of 23 students with ASD enrolled in two universities and four colleges, and 15 family members were explored in 15 semi-structured focus groups. Thematic analysis identified five themes: core ASD features, co-morbid conditions, transition, disclosure, and services and support. Most students felt educationally but not socially supported; most families felt support was poor in both areas. Transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
243
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(268 citation statements)
references
References 36 publications
10
243
0
15
Order By: Relevance
“…Students in this study were predominantly enrolled in postsecondary education and, as such, it will be important to determine if these findings apply to students with ASD still facing the transition out of high school. The themes that emerged from the focus groups converged with those identified from the survey data and, collectively, these data provide a complementary perspective (primarily that of parents and school personnel), to recent research that focused on the needs as identified by postsecondary students (e.g., Cai & Richdale, 2016). These preliminary findings offer early guidance to the field with respect to what should be included in programs designed to promote successful transition to postsecondary school for students with ASD.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Students in this study were predominantly enrolled in postsecondary education and, as such, it will be important to determine if these findings apply to students with ASD still facing the transition out of high school. The themes that emerged from the focus groups converged with those identified from the survey data and, collectively, these data provide a complementary perspective (primarily that of parents and school personnel), to recent research that focused on the needs as identified by postsecondary students (e.g., Cai & Richdale, 2016). These preliminary findings offer early guidance to the field with respect to what should be included in programs designed to promote successful transition to postsecondary school for students with ASD.…”
Section: Discussionmentioning
confidence: 59%
“…They found that students tended to receive considerable academic supports and accommodations, but lacked supports for social and emotional difficulties. Most recently, Cai and Richdale (2016) conducted focus groups with 23 students with ASD in postsecondary education and 15 family members. They found that students perceived receiving better educational than social supports, whereas family members reported inadequate supports in both the academic and social domains.…”
mentioning
confidence: 99%
“…Fortunately, there is an abundance of tools, programmes and apps that young adults may use on their personal computers, tablets or smartphones to support the acquisition of essential skills needed in secondary school, college and adulthood (for example, social skills, executive functioning, mental health; Cai & Richdale, 2016;Grogan, 2015). Fortunately, there is an abundance of tools, programmes and apps that young adults may use on their personal computers, tablets or smartphones to support the acquisition of essential skills needed in secondary school, college and adulthood (for example, social skills, executive functioning, mental health; Cai & Richdale, 2016;Grogan, 2015).…”
Section: Implications For Practicementioning
confidence: 99%
“…These difficulties include atypical sensory processing, inflexibility, executive function difficulties, challenges engaging in self-advocacy, social difficulties, depression, and anxiety (Glennon, 2001; Van Bergeijk et al, 2008; White et al, 2011; Schindler et al, 2015; Cai and Richdale, 2016). The stress that most students experience when transitioning into college may be compounded for autistic students, as difficulty in coping with change is part of the diagnostic criteria for ASD.…”
Section: Introductionmentioning
confidence: 99%
“…They stress the importance of individualized supports, such as mentoring, to help students on the spectrum develop self-advocacy, social, and executive functioning/self-regulation skills. However, only a few studies have directly assessed the needs and experiences of more than a few college students on the spectrum (Gelbar et al, 2014; Van Hees et al, 2015; Cai and Richdale, 2016; Roberts and Birmingham, 2017). …”
Section: Introductionmentioning
confidence: 99%